Food Safety, Security, Sustainability and Nutrition as Priority Objectives of the Food Sector - Raposo, António; Ramos, Fernando; Raheem, Dele; Carrascosa Iruzubieta, Conrado Javier; Saraiva, Ariana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The future food systems will have to provide food and nutrition security while facing unprecedented sustainability challenges: this underlines the need for a transition to more sustainable food systems. Taking into account these premises and considering the complexity of food systems, this book aims to present original research articles, reviews, and commentaries concerning the following:Advancements in food and beverage;Dietary supplements, nutraceuticals, and functional food;Food allergy and public health;Food and nutritional toxicology;Food biotechnology and food processing;Food microbiology and food safety;Food packaging;Food safety and food inspection;Food security and environmental impacts;Food waste management;Nutrition and metabolism;Sustainable food systems and agro-ecological food production.